Can we prevent the occurrence of stroke in patients admitted with non-ST-segment elevation myocardial infarction?. (11th May 2022) - Paula, S; Santos, M; Santos, H; Almeida, I; Figueiredo, M; Almeida, S; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardio-cerebral vascular diseases are a leading cause of deaths worldwide. Stroke is a potential complication in high-risk patients who had non-ST-segment elevation myocardial infarction (NSTEMI). Purpose: Identify high-risk patients with stroke and their prognosis in the setting of NSTEMI. Methods: Based on a multicenter retrospective study, data collected from admissions between January 2013 and January 2020. Patients without data on previous cardiovascular history or uncompleted clinical data were excluded. Patients were divided in 2 groups (G): G1 – patients who suffered stroke; G2 - patients without stroke. Logistic regression and survival analysis were performed. Results: 7180 patients were admitted with NSTEMI, stroke occurred in 35 patients (0.49%). Regarding epidemiological and past history G1 was older (72±9 vs 66±12, p= 0.004), had more females (54.3% vs 45.75, p<0.001), had higher rates of type 2 diabetes mellitus (51.3% vs 35.2%, p=0.05), previous strokes / transient ischemic attack (24.2% vs 7.0%, p=0.007) and dementia (3.3% vs 0.8%, p<0.001). Arterial hypertension (77.1 vs 72.8%, p=0.56), dyslipidaemia (61.8% vs 63.0%, p=0.88) and smoking (17.6% vs 26.0%, p=0.27) were similar between groups. Patients who presented with chest pain (72.7% vs 92.0%, p<0.001) and patients who were not revascularized were more likely to suffer a stroke (43.3% vs 17.5%, p<0.001). Logist regression only confirmed that females were more likely to have a stroke (p<0.001, OR 4.13, CI 1.87-9.15) and patients who presented with chest pain (p=0.001, OR 0.23, CI 0.10-0.54). One year event-free survival was higher in patients who did not have stroke (95.3% vs 80.0%, p=0.005, OR 4.50, CI 1.43-14.15) Conclusion: Since sex gender and form of presentation of NSTEMI are not modifiable factors we cannot prevent strokes from happening in the context of NSTEMI.